Thick film paste preparation and characterization of BaTiO3 for humidity sensor - Wan Zaki, Wan Suhaimizan; Wagiran, Rahman; Mohd Noor, Samsul Bahari; Shaari, Abdul Halim (Federation of Engineering Institutions of Islamic Countries, 2006)
A dielectric material of BaTiO3 powder was prepared using solid state reaction from raw materials; BaCO3 and TiO2. A study was conducted to prepare the BaTiO3 thick film paste by mixing the organic vehicle and the sintered powder in ratio of 30:70. The organic vehicle was formed from suspending ethyl cellulose resins into terpineol solvent in a specific ratio. The paste was printing onto ceramic substrate by using DEK J1202 thick film screen printer machine. The recipe and the process in producing BaTiO3 thick film paste was then established. The electrical properties of screen-printed BaTiO3 were investigated in an interdigitated electrode pattern. Experimental results show that the smaller gap between two adjacent electrodes gives higher capacitance and lower resistance value, thus provide better response time in detecting capacitor changes for sensor application. An equivalent circuit to represent the dialectic mechanism of the BaTiO3 thick film sample has also been established.